PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Nathania Gisela; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure on the financial performance of basic materials companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Financial performance is measured using Return on Assets (ROA), while audit quality serves as a moderating variable and firm size is included as a control variable. The study is based on legitimacy theory and agency theory, which suggest that ESG disclosure can enhance corporate legitimacy, reduce information asymmetry, and increase investor confidence, while high audit quality improves the credibility of corporate information. Using a quantitative research approach, the study analyzes secondary data obtained from annual reports and the Bloomberg Terminal. The sample consists of 23 companies with a total of 92 firm-year observations selected through purposive sampling. Data analysis is conducted using panel data regression and Moderated Regression Analysis (MRA) to evaluate both the direct effect of ESG disclosure on financial performance and the moderating role of audit quality. The results reveal that ESG disclosure has a positive and significant impact on corporate financial performance. More specifically, the environmental and social dimensions of ESG contribute significantly to improving ROA, indicating that companies with stronger environmental and social practices tend to achieve better financial outcomes. In contrast, the governance dimension does not show a significant effect on financial performance. Furthermore, the findings demonstrate that audit quality strengthens the positive relationship between ESG disclosure and financial performance, suggesting that credible and high-quality audits enhance stakeholder trust in ESG information and increase its value in improving corporate performance. These findings highlight the importance of ESG practices and audit quality in supporting sustainable business performance and long-term value creation.